Az 1912. évi XXXVI. törvénycikk „A Debreczeni és a Pozsonyi Magyar Királyi Tudomány Egyetem felállításáról” szövege és miniszteri indokolása - P. Szabó, Béla (Gerundium, 2011)
The Text and Ministerial Preamble of Article XXXIV of 1912 ”About the Foundation of Hungarian Royal Universities in Debreczen and Pozsony”. The objective of this source publication is nothing else but the bill and its preamble, through which in 1912 the universities of Debrecen and of Pozsony, respectively, came to be established. The preamble signed by Minister of Religion and Public Education János Zichy well reflects all the aspirations and controversies which characterized Hungarian educational and higher educational policy at the end of the 19th century, and the path, punctuated by manifestations of zeal and regression, finally led to the foundation of the third and fourth university in Hungary. The thorough preliminary professionalism pervading the preamble which, despite the disunity of the political spectrum, made a success of the bill can be regarded as exemplary.